2020
DOI: 10.1038/s41598-020-61636-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of mouse-tracking software to detect faking-good behavior on personality questionnaires: an explorative study

Abstract: the aim of the present study was to explore whether kinematic indicators could improve the detection of subjects demonstrating faking-good behaviour when responding to personality questionnaires. one hundred and twenty volunteers were randomly assigned to one of four experimental groups (honest unspeeded, faking-good unspeeded, honest speeded, and faking-good speeded). Participants were asked to respond to the MMPI-2 underreporting scales (L, K, S) and the PPI-R Virtuous Responding (VR) scale using a computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
(47 reference statements)
6
20
0
Order By: Relevance
“…The present research demonstrated that IS in the elderly is also correlated with emotive/affective variables, such as worry and self-esteem, confirming its multifaceted nature. This finding was confirmed by the ML analysis [104,105], which underlined the importance of memory (predominantly) and all of the studied cognitive and emotive/affective variables in explaining IS in an elderly population.…”
Section: Discussionsupporting
confidence: 59%
“…The present research demonstrated that IS in the elderly is also correlated with emotive/affective variables, such as worry and self-esteem, confirming its multifaceted nature. This finding was confirmed by the ML analysis [104,105], which underlined the importance of memory (predominantly) and all of the studied cognitive and emotive/affective variables in explaining IS in an elderly population.…”
Section: Discussionsupporting
confidence: 59%
“…ML algorithms automatically learn information from a set of data and make predictions on unseen data without being explicitly programmed to do so. ML techniques have been shown to be particularly useful in predicting human behavior, including high-risk behavior [ 48 , 49 , 50 , 51 ]. Indeed, one of the main advantages of ML is that it enables inferences to be made at the individual level, whereas traditional statistical methods focus primarily on the group level [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overwhelming proportion of child custody evaluations involve psychometric measures, which are predominantly used to assess the personality characteristics and functioning of litigants. One such measure, the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) (Butcher et al, 2001), is a well-established psychological instrument that is frequently used in forensic assessment (Burla et al, 2019; Mazza et al, 2019a; Mazza, Monaro et al, 2019b; Mazza et al, 2019c; Mazza, Monaro et al, 2020; Roma et al, 2013; Roma et al, 2016; Roma et al, 2018; Roma et al, 2019a; Roma et al, 2019b; Roma et al, 2020). Only two studies have analyzed the MMPI-2 profiles of PA subjects.…”
Section: Introductionmentioning
confidence: 99%